Experimental and Theoretical Study of the Effects of Rare Earth Elements on Growth and Chlorophyll of Alfalfa (Medicago sativa L.) Seedling - Song, Kexiao; Gao, Jinzhu; Li, Shuo; Sun, Yunfu; Sun, Haoyang; An, Baiyu; Hu, Tianming; He, Xueqing (Frontiers in Plant Science, 2021)
Rare earth elements (REEs) of low concentration are usually beneficial to plant growth, while they are toxic at high concentrations. The effects of treatment with lanthanum (La) (10 and 20 μM), cerium (Ce) (10 and 20 μM), and terbium (Tb) (10 and 20 μM) on seedling growth of alfalfa (Medicago sativa L.), which is one of the most important perennial leguminous forages in the world, were studied. The results showed that all three REE treatments quickened the germination of seeds. The length of shoot under La (20 μM) treatment was significantly shortened (P < 0.05). In addition, treatment with La, Ce, and Tb had a “hormesis effect” on root length. There was a significant decrease in chlorophyll content on treatment with the three REEs, and the degree of decline was in the order of La < Ce < Tb, under the same concentration. In vitro experiments and quantum chemical calculations were further performed to explain why the treatments with REEs reduced the chlorophyll content. In vitro experiments showed that La, Ce, and Tb treatments reduced the absorbance of chlorophyll, and the decrease followed in the order of La > Ce > Tb. Quantum chemical calculations predicted that the decrease in absorption intensity was caused by the reactions between La, Ce, Tb, and chlorophyll, which formed lanthanides-chlorophyll; and there were five types of stable lanthanides-chlorophyll. In conclusion, the decrease in chlorophyll content on treatment with REEs was caused by the change in chlorophyll structure.